2020
DOI: 10.1016/j.abd.2020.04.011
|View full text |Cite
|
Sign up to set email alerts
|

Allergic contact dermatitis to cosmetics: retrospective analysis of a population subjected to patch tests between 2004 and 2017

Abstract: Background Cosmetics are part of the daily life of the population, and their use can lead to allergic contact dermatitis. Objectives To assess the profile of patients diagnosed with allergic contact dermatitis to cosmetics treated at a referral center for 13 years, as well as the characteristics of the clinical picture and allergens involved. Methods This was a retrospective study, with analysis of medical records of patients attended at this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 14 publications
(26 reference statements)
1
9
0
Order By: Relevance
“…For instance, a 13-year review of 1045 medical records in Brazil reported that 57.5% of patch-tested patients had a final diagnosis of ACD. 46 This is similar to North American findings; the most recent NACDG analysis (2017-2018) found that 65.4% of 4947 patchtested patients had at least 1 positive patch test reaction, and 50.4% had a final primary diagnosis of ACD. 47 Although the prevalence of ACD has not been shown to significantly differ across race and ethnic populations, the prevalence of AD has been found to vary widely across different ethnic groups.…”
Section: Race Ethnicity and Dermatitis Prevalencesupporting
confidence: 84%
See 1 more Smart Citation
“…For instance, a 13-year review of 1045 medical records in Brazil reported that 57.5% of patch-tested patients had a final diagnosis of ACD. 46 This is similar to North American findings; the most recent NACDG analysis (2017-2018) found that 65.4% of 4947 patchtested patients had at least 1 positive patch test reaction, and 50.4% had a final primary diagnosis of ACD. 47 Although the prevalence of ACD has not been shown to significantly differ across race and ethnic populations, the prevalence of AD has been found to vary widely across different ethnic groups.…”
Section: Race Ethnicity and Dermatitis Prevalencesupporting
confidence: 84%
“…International cohorts demonstrate that more than half of patients presenting for patch testing have a final diagnosis of ACD. For instance, a 13-year review of 1045 medical records in Brazil reported that 57.5% of patch-tested patients had a final diagnosis of ACD 46 . This is similar to North American findings; the most recent NACDG analysis (2017–2018) found that 65.4% of 4947 patch-tested patients had at least 1 positive patch test reaction, and 50.4% had a final primary diagnosis of ACD 47 …”
Section: Why Is This Important?mentioning
confidence: 53%
“…20 A few other reports have also confirmed that both AD and female gender give a significant increased risk of adverse reactions to cosmetic products. 17,18,20,21 It is possible that the patients in our study are selected and may have refrained from using eg, fragranced cosmetics from an early age, or more likely that the diagnosis of irritant contact dermatitis to cosmetics has been underestimated in our study, due to lack of diagnostic criteria.…”
Section: Database Studymentioning
confidence: 99%
“…Shampoos may contribute to a head and neck dermatitis, whereas deodorants may provoke axillary dermatitis, and, occasionally, more atypical localizations of ACD from FA/FRs (eg, leg dermatitis related to bronopol sensitization) have been reported 13,24 . Several cases of airborne ACD from FA, often presenting as severe facial edema, have been published due to its presence in hair‐straightening products (“Brazilian keratin treatments”), 43‐45 which may also lead to the release of FA into the air, and thus provoke mucosal and respiratory symptoms in both clients and hairdressers (eg, rhinoconjunctivitis and/or asthma 46 ). Among many other contact allergens, FA has also been associated with frontal fibrosing alopecia (FFA), especially due to its presence in hair‐straightening products 47 …”
Section: Clinical Picturementioning
confidence: 99%